Comparing the Impact of Food and Energy Price Shocks on Consumers : A Social Accounting Matrix Analysis for Ghana - Parra, Juan Carlos; Wodon, Quentin (World Bank, Washington, DC, 2012)
Many countries have been affected by food and oil price shocks. Rising energy costs have manifested themselves through higher prices of gas at the pump and through price increases for many other goods such as kerosene and transport. But in some countries there has also been some degree of protection for consumers for example when authorities have chosen to try to keep electricity tariffs affordable through implicit subsidies (which are unfortunately often poorly targeted). For food prices, the effect on consumers has often been more rapid than for oil-related products, as the increase in import prices have been typically fully passed on to consumers and has often been accompanied by increases in the prices of domestically produced foods. Recent attention has therefore rightly been focused on food prices, but the issue of oil prices is important as well. While food prices tend to have a larger direct impact on consumers due to the larger share of food in total household consumption, oil prices may have larger multiplier effects than food prices because oil-related products are used as intermediary products in many productive sectors. It therefore remains an open question as to whether the medium-term impact of food or oil prices is likely to be larger in any given country. It also remains open to question as to whether urban as opposed to rural households are most likely to be affected. While urban households are likely to rely on consumption of imported goods more than rural households, the weight of food and possibly oil-related products may well be larger in the consumption patterns of rural than urban households. Answering these questions may be useful to guide discussions on compensatory measures that governments can take to respond to the twin crisis of higher food and oil prices. In this context the objective of this paper is to provide a comparative analysis of the multiplier impact of both types of price shocks using a recent Social Accounting Matrix for Ghana. The paper finds that both the direct impacts of food prices and the indirect impacts of oil prices are potentially large, so that both should be dealt with by authorities when considering compensatory measures to protect households from higher consumer prices.